Pelatihan Penerapan Model Pembelajaran Berbasis Proyek pada Kurikulum Merdeka Belajar di SMP Negeri 1 Torgamba - Nurlina Ariani HRP; Eva Julyanti; Indah Fitria Rahma; Rosmidah Hasibuan; Zahara Saragih; Siti Suharni Simamora; , Sintya Lestari Sinulingga; Marlina Nasution (Pengelola Jurnal Politeknik Negeri Ketapang, 2023)
The implementation of Community Service (PkM) aims to improve teachers' ability to manage classroom learning by using a project-based learning model, especially in the independent learning curriculum. This type of PkM is a training activity and is followed by assistance in class with teachers and students of SMP Negeri 1 Torgamba. This community service is carried out by lecturers and students of FKIP, Labuhanbatu University. The results of the activity showed that the attitude of the teachers in receiving the training was very enthusiastic. To measure the success of PkM, mentoring is carried out by applying the learning model with teachers who have received training. The results of the activity show that learning outcomes and student learning activities increase by using a project-based learning model.